Structural elaboration of dicyanopyrazine: towards push-pull molecules with tailored photoredox activity - Hloušková, Zuzana; Klikar, Milan; Pytela, Oldřich; Almonasy, Numan; Růžička, Aleš; Jandová, Veronika; Bureš, Filip (ROYAL SOC CHEMISTRY, 2019)
As an extension of the successful dicyanopyrazine photoredox catalysts, a series of X-shaped push-pull molecules with a systematically altered structure were designed and facilely synthesized; their structure-property relationship was elucidated in detail via experimental as well as theoretical calculations. Dicyanopyrazines are proven to be powerful photoredox catalysts with a push-pull arrangement that allows facile property tuning by interchanging a particular part of the D-pi-A system. Changing the mutual position of the cyano acceptors and the methoxy, methylthio and thienyl donors as well as modifying the linker allowed wide tuning of the fundamental properties of the catalysts. Contrary to the currently available organic photoredox catalysts, we provided a series of catalysts based on a pyrazine heterocyclic scaffold with easy synthesis and further modification, diverse photoredox characteristics and wide application potential across modern photoredox transformations. The photoredox catalytic activities of the target catalysts were examined in a benchmark cross-dehydrogenative coupling and novel and challenging annulation reactions.
Strukturální modifikace dikyanopyrazinu: push-pull molekuly s cílenou fotoredoxní aktivitou
Keywords: light-mediated synthesis; merging photoredox; aromaticity index; n-methylanilines; carboxylic-acids; metal-free; catalysis; derivatives; cyclization; tetrahydroquinolines; methylaniliny; karboxylové kyseliny; katalýza; cyklizace; tetrahydrochinoliny